THE RELATIONSHIP BETWEEN LEARNERS PERCEPTION ON COMPETENCIES OF SCIENCE TEACHER WITH MOTIVATION AND LEARNING OUTCOMES OF STUDENTS IN JUNIOR HIGH SCHOOL IN TUAL CITY - Asmirah, Nurul; Hala, Yusminah; Ramlawati, Ramlawati (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Teacher competence plays an important role in improving students learning outcomes. This study aims to determine the relationship between (1) students perceptions about the science teacher competence and students motivation of Junior High School in the Tual City, (2) students perceptions about the science teacher competence and students learning outcome of Junior High School in Tual City, (3) Students learning motivation and learning outcomes of Junior High School in Tual City. Study data were obtained from 124 students and three teachers from three schools. The results showed that (1) There is a significant relationship between students perceptions about the science teacher competence and students motivation of Junior High School in the Tual City, (5) There is no significant relationship between students perceptions about the science teacher competence and students learning outcome of Junior High School in Tual City, (6) There is no significant relationship between students learning motivation and learning outcomes of Junior High School in Tual City. Students perception on science teacher competence and learning motivation are not the only factors that affect learning outcomes, but there are several factors that influence the learning outcomes of students.